2011
DOI: 10.1002/cae.20303
|View full text |Cite
|
Sign up to set email alerts
|

Research regarding the implementation of an interactive application for educational improvement of engineering drawing

Abstract: In the current European university reform teacher-based education is replaced by another form of teaching, which is more focused on the students. To facilitate this task, a self-learning-oriented application called AIMEC-DT was developed. This article discusses, by means of an educational experience, the advantages of using these types of interactive tools adapted to achieve that goal. The results obtained allow us to conclude that their use can be a significant improvement in teaching in engineering. ß

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…3D approaches try to create visualisations that are closer to real‐world metaphors: the user is able to rotate and move 3D objects and navigate inside a 3D world . These tools should provide not only effective visual representations, but also effective interaction styles to ease exploration .…”
Section: Factors To Consider In the Design Of E‐learning Platforms Fomentioning
confidence: 99%
“…3D approaches try to create visualisations that are closer to real‐world metaphors: the user is able to rotate and move 3D objects and navigate inside a 3D world . These tools should provide not only effective visual representations, but also effective interaction styles to ease exploration .…”
Section: Factors To Consider In the Design Of E‐learning Platforms Fomentioning
confidence: 99%
“…The following studies (some with contradictory results) on the effectiveness of the various methodologies that employ EVEs for the development of SVA, fundamentally CAD and multimedia applications, may be highlighted: ‐ Sorby and Baartmans , made it clear that the completion of exercises (where appropriate using I‐DEAS software) improved the learning processes of students with greater learning difficulties. ‐ Rafi et al found significative evidence that the use of Web3D applications as well as 3D pedagogic tools in VRML format improved the development of spatial skills. ‐ Koch demonstrated that there were no significant differences between sketching and solid‐modeling design methods used to find solutions to technical problems ( P = 0.752). ‐ Konukseven compared traditional methods on an Engineering Graphics course with a teaching method that depended on 3D models in VRML format. The results showed that both methods were of the same quality. ‐ Martín‐Gutiérrez et al verified that the combined use of a multimedia application with simultaneous 3D manipulation of the objects and its main projection planes, improved SVA levels in geometry. ‐ Pando et al concluded that the use of interactive tools in the teaching of Engineering Drawing significantly improved the results of traditional learning in this subject. …”
Section: Introductionmentioning
confidence: 97%
“…In fact, one of the main problems highlighted by these analyses is the students’ difficulties in understanding the three‐dimensional shape of objects starting from their two‐dimensional representations or their poor sketching abilities . In the literature, there are several examples of analysis and optimization of this type of problems usually resolved with the creation of ad hoc courses, with the development of specific software tools, or the use of 3D CAD applications to improve the understanding of the spatiality of three‐dimensional objects . Among the latest trends, we note the massive use of augmented reality techniques as an aid to visualization [18,40].…”
Section: Trends and Innovations In Teaching Td And/or Engineering Gramentioning
confidence: 99%